Student Gender and Support by Compassion International Influences Achievement Goal Orientation among Adolescents in South-western Uganda. - Ndyareeba, Eunice; Zanna, Clay; Biirah, Judith; Kasawo, Henry Kibedi (Kabale University, 2024)
The adoption of achievement goal orientation is a crucial factor in shaping an individual's attitudes and behaviors toward learning. The aim of this study was to investigate the impact of gender and support from Compassion International on the adoption of achievement goal orientation (AGO). The study used a parallel mixed methods approach to sample 510 adolescent students aged 12 -21 years were included in the study. Both Compassion International support beneficiaries and nonbeneficiaries were recruited for the study. The Mann-Whitney Test for Differences yielded statistically significant findings regarding the adoption of achievement goal orientation about gender and support from Compassion International. Mann-Whitney U Test was used because it was suitable for comparing the overall distribution of participants across gender and Compassion International support since the numbers of respondents within each of the two categories were not uniformly distributed. The adoption of mastery approach (MAP) and performance-avoidance goals (PAV) was found to be predicted by Gender, whereas mastery goals (approach and avoidance) and performance approach goals (PAP) were predicted by support from Compassion International. The findings of the study offer valuable insights into the possible gender-based discrepancies in achievement goal orientation and underscore the significance of compassion support in promoting achievement goal orientation that results in self-skill enhancement. This information can serve as a valuable resource for educators, parents, and policymakers in formulating effective approaches that tackle gender-based disparities as well as integrating external support initiatives by non-governmental organizations within the educational framework to foster fair and enduring educational outcomes.